AN INNOVATIVE APPROACH TO EDUCATION AND TRAINING - Sattorov Vaxob Naqshbandovich; Быстрова Юлия Александровна (American Journals Publishing, 2024)
This article explores innovative approaches to education and training, focusing on integrating technology, personalized learning, and experiential methods. It analyzes current literature, presents methodologies, and discusses the results and implications for future educational practices.
Keywords: Innovative education, personalized learning, experiential learning, educational technology, training methodologies.